Tidal airway closure in asthma and COPD - Claudio Tantucci; Laura Pini (Monaldi Archives for Chest Disease, 2016)
Functional closure of small airways can occur during tidal breathing above functional residual capacity (FRC) both in asthma and COPD patients, especially during exacerbations. Such event has several noxious consequences on gas exchange, airway hyperresponsiveness and mechanical stress and strain within lung tissue and airway wall, mostly due to increase in ventilation heterogeneity. The availability of simple functional tests based on sequential measurements of lung volumes (i.e.: FRC), by plethysmography and dilutional techniques may reveal and monitor easily tidal airway closure that can be and should be treated with the aim of abolishing or at least reducing this dangerous condition.